Transient stainless-steel dissolution and its consequences on ex-situ bipolar plate testing procedures. (1st January 2020) - Li, Xuejie; Zhou, Peng; Ogle, Kevin; Proch, Sebastian; Paliwal, Manas; Jansson, Anna; Westlinder, Jörgen
Abstract: Stainless steels, due to their scalability, formability, and cost effectiveness, are, today, used as bipolar plates in proton-exchange membrane fuel cells (PEMFCs). The release of cationic metal species during fuel cell operation may have an impact on fuel cell durability if accumulated in the ionomer phase (membrane electrode assembly). However, the mechanisms and time scales of this release from stainless-steel surfaces are not fully understood, hence, a systematic study was carried out. Time-resolved dissolution measurements of bright-annealed stainless steels in a simulated fuel cell show measurable ion dissolution exclusively under changing potentials (passive-transpassive-passive transition, transient transpassivity, 100s). Together with shielded (decoupled) bipolar plates these findings suggest the absence of continued metal ion release from stainless-steel bipolar plates and, in turn, ultra-low Fe dissolution. Moreover, prolonged potentiostatic tests seem unsuitable since they will probe the passive state with low or absent dissolution for the most part. Graphical abstract: The C Major Chord of Stainless-Steel Dissolution : Stainless-steel dissolution takes place through triads (passive-transpassive-passive transitions) that are similar to musical chords. Image 1 Highlights: Stainless-steels exhibit highly transient dissolution properties. Dissolution via passive-transpassive-passive transitions (≈100 s). Decoupled bipolar plate potentials will lead to ultra-low metal ion dissolution. Potentiostatic ex -situ screening of stainless-steel bipolar plates seems unsuitable.